Using Gamification and Digital Technology to Enhance Language Learning - Valijonovna, Bafoyeva Rokhila; Ziyodullo qizi, Djurayeva Malika (Journal of Innovation in Education and Social Research, 2024)
Language learning is a challenging yet rewarding process that goes far beyond memorizing vocabulary and translations. It involves mastering grammar, understanding cultural nuances, and developing communication skills. This paper explores the role of gamification and digital technology in enhancing language learning for students and adults alike. Gamified tools such as Kahoot!, Quizizz, and Drimify provide engaging and structured approaches to learning, while platforms like Canva and ChatGPT support educators in creating dynamic and interactive content. Additionally, leveraging online resources and social media enables learners to practice and immerse themselves in authentic language experiences. These innovative tools not only make language acquisition more effective but also foster long-term motivation, autonomy, and enjoyment in the learning journey.